PERAN PEMERINTAH NAGARI DALAM PENGEMBANGAN WISATA KAMPUNG KOPI DI NAGARI KOTO TUO KECAMATAN SUNGAI TARAB KABUPATEN KAMPAR 2023 - Kurniawan, Ikhbal; ', Wazni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
The role of the village government in developing coffee village tourism in Nagari Koto Tuo, Sungai Tarab District, Tanah Datar Regency has the potential to be developed into a coffee village that will provide benefits to the local community. Nagari Koto Tuo has an increasing natural tourist attraction and has many coffee industries that are managed from generation to generation from ancestors so that it has unique coffee characteristics. A total of 177 coffee powder business trademarks are registered which makes Nagari Koto Tuo a coffee powder producing village. However, it has not yet achieved maximum results such as the incomplete tourism facilities such as the unavailability of rest areas (places) for visiting tourists. This study aims to determine how the role of the Koto Tuo Nagari Government in developing coffee village tourism. The method used in this research is a qualitative method using a descriptive approach. The theory used in this study uses the theory of Titana and Gayatri (2005) which has 3 indicator components, namely motivator, facilitator and dynamizer. The results of the study state that the role of the Government of Nagari Koto Tuo, Sungai Tarab District, Tanah Datar Regency is still not going well in the development of Nagari Koto Tuo coffee village tourism in accordance with the indicators set by the research. The inhibiting factor is human resources (HR) who still lack awareness or are still not working with the government. Keywords: Role, Nagari Government, Development